2003
DOI: 10.1590/s1413-70542003000300001
|View full text |Cite
|
Sign up to set email alerts
|

Absorção e translocação de silício em mudas de eucalipto cultivadas em latossolo e cambissolo

Abstract: Com o objetivo de estudar a absorção e a translocação de Si em mudas de Eucalyptus grandis W. Hill. Ex Maiden cultivadas em amostras de Latossolo Vermelho distrófico e de Cambissolo Háplico Tb distrófico, foram realizados dois experimentos em casa-de-vegetação. Cada solo foi submetido a três incubações seqüenciais para a aplicação dos tratamentos: a) CaCO3+MgCO3 para manter o pH em torno de 6,0; b) fertilização básica com macro e micronutrientes; c) seis doses de Si (CaSiO3). As plantas foram cultivadas em vas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
6
0
9

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 14 publications
(14 reference statements)
4
6
0
9
Order By: Relevance
“…These results are similar to those found by Carvalho et al (2003) in eucalyptus seedlings. These authors have concluded that although responsive to Si, eucalyptus cannot be considered an accumulator species, as most dicotyledons can.…”
Section: Nutrients Plant Partssupporting
confidence: 91%
See 2 more Smart Citations
“…These results are similar to those found by Carvalho et al (2003) in eucalyptus seedlings. These authors have concluded that although responsive to Si, eucalyptus cannot be considered an accumulator species, as most dicotyledons can.…”
Section: Nutrients Plant Partssupporting
confidence: 91%
“…However, for eucalyptus, Carvalho et al (2003) found greater retention of Si in the roots instead of shoots after 60 days. This behavior would possibly occur in coffee plants if the experimental period were greater, since for dicotyledons it is common to find higher accumulation of Si in the roots.…”
Section: Nutrients Plant Partsmentioning
confidence: 78%
See 1 more Smart Citation
“…Analisando-se a relação entre o teor de Si na parte aérea e na raiz de eucalipto, Carvalho et al (2003) observaram a retenção desse elemento nas raízes, pois a relação PA/R começou a reduzir-se a partir de 60 dias após o sua transplantio, indicando diminuição da eficiência de sua translocação com o aumento da idade das plantas. De maneira semelhante, Pozza (2004) verificou que a cultivar de café Mundo Novo apresentou maior relação PA/R para N, P, K, Ca, Mg, S, B, Mn e Si, justificando a maior capacidade de translocar esses nutrientes das raízes para a parte aérea.…”
Section: Relação Do Acúmulo De Nutrientes Entre a Parte Aérea E As Raunclassified
“…The second reason is that soluble Si acts as a modulator of host resistance to pathogens, activating some defense mechanisms (Ma and Yamaji, 2006). SiO 2 combines with water molecules (2H 2 O), forming H 4 SiO 4 which can be considered as a "water deposit" (Carvalho et al, 2003), being important during periods of water stress by providing water to the plants, since water is the most limiting factor for plant growth in tropical regions (Stape et al, 2004).…”
Section: Introductionmentioning
confidence: 99%